Memperkuat Eksistensi Pendidikan Islam Di Era 4.0 - Sigit Priatmoko (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
This paper seeks to promote the need for massive reform in the body of Islamic education. This reform is necessary for Islamic education to respond to the challenges and demands of the changing age. In addition, this paper also seeks to offer a solute offer to Islamic education in the face of the Industrial Revolution Era 4.0. As we all know, the era of 4.0 has a broad impact in all areas of life, not least in the field of education. The era that gave birth to this phenomenon disruption requires the Islamic education world to participate in adjusting. Islamic education graduates are now faced with new challenges, demands, and needs that have never existed before. So it is necessary to update and innovate the system, governance, curriculum, competence of human resources, facilities and infrastructure, culture, work ethic, and others. Otherwise, Islamic education will be increasingly lagging and obsolete. Therefore, it is necessary to find definite steps for Islamic education in order to remain competitive in this disruption era. Solutive step is to participate disruption themselves.